Research on prediction and realization path of carbon peak of construction industry based on EGM-BP model - Dai, Dawei; Li, Kexin; Zhao, Shuhang; Zhou, Biao (Frontiers in Energy Research, 2022)
In order to actively respond to the global climate and environmental challenges, and to help achieve the goal of carbon peaking and carbon neutrality, China aims to achieve carbon peaking by 2030. As the main contributor of energy consumption, construction industry transformation is imminent. This paper focuses on the development trend of carbon emissions in Anhui construction industry in the next 20 years, and how to help Anhui construction industry achieve the carbon peak target. The research process and conclusions are as follows: (1) Through literature combing and gray correlation analysis, seven important factors affecting the construction industry are identified. (2) The gray prediction EGM(1,1) model was adopted to forecast the carbon emissions of the construction industry in Anhui Province from 2021 to 2040. The research results show that carbon emissions will increase year by year in the next 20 years. (3) The EGM-BP neural network model was used to further predict the carbon emissions from the construction industry in 2021-2040. It is expected that the carbon emissions from construction industry in Anhui Province will show an "inverted U" trend in the next 20 years, and is expected to reach its peak in 2031, after which it will start to decline. Based on the results of the above study, we provide support paths for achieving the carbon peak in the construction industry from the perspective of improving and developing the construction system, and provide policy suggestions for relevant departments to accelerate the construction industry carbon peak construction in Anhui Province.